ASSESSMENT OF GENETIC DIVERSITY IN DIVERSE GENOTYPES OF EGG PLANT (SOLANUM MELONGENA L.) USING RAPD MARKERS - S. MISHRA; M. SINGH; R. S. SHARMA (The Bioscan, 2014)
The present study was aim to analyze genetic diversity among diverse genotypes egg plant using Random Amplified Polymorphic DNA (RAPD) technique. Twenty RAPD primers were used to amplify genomic DNA from 24 brinjal genotypes. Out of 20 primers, of which only 5 primers (6.5%) showed polymorphism and remaining 15 showed monomorphism. The DNA fragments of various sizes ranging from 500 bp to 1300 bp were amplified in various egg plant genotypes. Estimates of genetic distance (GD) ranged from 0.27 to 1.05. Cluster analysis showed that genotypes were clustered in two groups A and B on the basis of distinct and significant genotypes. The UPGMA dendrogram based on genetic distance segregated the 24 genotypes fall into six clusters. Thus the genotypes included in the diverse clusters could be used as a parent for hybridization in order to obtain a high heterotic response and better segregates in eggplant. Therefore, identification of genetically distinct varieties using RAPD marker could be a potential tool for Eggplant improvement.